1996
DOI: 10.1037/0735-7044.110.5.1187
|View full text |Cite
|
Sign up to set email alerts
|

Increased histidine preference during specific alteration of rhythm of environmental temperature stress in rats.

Abstract: It has been reported that specific alteration of rhythm of environmental temperature (SART) stress induces various physiological changes. In this study, changes in taste preference during SART stress were investigated in rats. Rats were given free access to six amino acid solutions, saline, and water in a choice paradigm. During SART stress, daily food intake increased significantly by 50% whereas the rate of body weight gain decreased significantly to one third that observed during the prestress baseline peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
(40 reference statements)
2
3
0
Order By: Relevance
“…This interpretation is of interest when considering the functional implication of these two brain areas. For instance, hyperphagia is a unique characteristic of chronic cold stress including repeated cold stress (Bing et al 1998;Hata et al 1984aHata et al ,b, 1988aKondoh et al 1996;Leung and Horwitz 1976;Morrison 1981;Okano et al 1993;Snyder and Stricker 1985), which can be clearly distinguished from the anorexia induced by severe acute stress conditions (Morley and Levine 1982;Shimizu et al 1989). Consistent with the previous studies (Hata et al 1984a(Hata et al ,b, 1988aKondoh et al 1996;Okano et al 1993), in the present study we also observed an increase in food intake in the rats exposed to repeated cold stress.…”
Section: Effect Of Repeated Cold Stress On Spontaneous Firing Rates Osupporting
confidence: 90%
See 4 more Smart Citations
“…This interpretation is of interest when considering the functional implication of these two brain areas. For instance, hyperphagia is a unique characteristic of chronic cold stress including repeated cold stress (Bing et al 1998;Hata et al 1984aHata et al ,b, 1988aKondoh et al 1996;Leung and Horwitz 1976;Morrison 1981;Okano et al 1993;Snyder and Stricker 1985), which can be clearly distinguished from the anorexia induced by severe acute stress conditions (Morley and Levine 1982;Shimizu et al 1989). Consistent with the previous studies (Hata et al 1984a(Hata et al ,b, 1988aKondoh et al 1996;Okano et al 1993), in the present study we also observed an increase in food intake in the rats exposed to repeated cold stress.…”
Section: Effect Of Repeated Cold Stress On Spontaneous Firing Rates Osupporting
confidence: 90%
“…For instance, hyperphagia is a unique characteristic of chronic cold stress including repeated cold stress (Bing et al 1998;Hata et al 1984aHata et al ,b, 1988aKondoh et al 1996;Leung and Horwitz 1976;Morrison 1981;Okano et al 1993;Snyder and Stricker 1985), which can be clearly distinguished from the anorexia induced by severe acute stress conditions (Morley and Levine 1982;Shimizu et al 1989). Consistent with the previous studies (Hata et al 1984a(Hata et al ,b, 1988aKondoh et al 1996;Okano et al 1993), in the present study we also observed an increase in food intake in the rats exposed to repeated cold stress. Previous behavioral and neurophysiological studies have suggested that the LHA and ventromedial hypothalamic nucleus (VMH, a part of the MHA defined in the present study) control feeding behavior in opposing manners; the LHA is thought to be a feeding center and the VMH together with the PVN are satiety centers (Delgado and Anand 1953;Leibowitz 1986;Oomura et al 1967Oomura et al , 1969Shimizu et al 1987;Smith 1956;Winn et al 1984).…”
Section: Effect Of Repeated Cold Stress On Spontaneous Firing Rates Osupporting
confidence: 90%
See 3 more Smart Citations